Chromium contamination and effect on environmental health and its remediation: A sustainable approaches. (1st May 2021) - Prasad, Shiv; Yadav, Krishna Kumar; Kumar, Sandeep; Gupta, Neha; Cabral-Pinto, Marina M.S.; Rezania, Shahabaldin; Radwan, Neyara; Alam, Javed
Abstract: Chromium (Cr) is a trace element critical to human health and well-being. In the last few decades, its contamination, especially hexavalent chromium [Cr(VI)] form in both terrestrial and aquatic ecosystems, has amplified as a result of various anthropogenic activities. Chromium pollution is a significant environmental threat, severely impacting our environment and natural resources, especially water and soil. Excessive exposure could lead to higher levels of accumulation in human and animal tissues, leading to toxic and detrimental health effects. Several studies have shown that chromium is a toxic element that negatively affects plant metabolic activities, hampering crop growth and yield and reducing vegetable and grain quality. Thus, it must be monitored in water, soil, and crop production system. Various useful and practical remediation technologies have been emerging in regulating chromium in water, soil, and other resources. A sustainable remediation approach must be adopted to balance the environment and nature. Graphical abstract: Image 1 Highlights: Strategies for addressing all aspects of Cr − contamination and its remediation. Reducing the levels of Cr(VI) in wastewaters and provide alternative sources. Cr − uptake, translocation, and toxicity on plant and human were discussed. Cr − tolerance mechanisms in plants and their impacts on growth and development were reviewed. Limitations, strategies, and future policy research needed for safe disposal mechanisms have been elaborated.